TRANSFORMATION OF SCHOOL LITERACY IN THE MERDEKA CURRICULUM: STRATEGIES AND IMPLEMENTATION FOR SHAPING READING CHARACTER IN THE BOARDING SCHOOLS - Ghazali, Masrur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The school literacy movement is an important matter in the advancement of broad knowledge. School literacy activities are the ability to access, understand, and review the books they read. There are three ways to implement GLS, namely: the first is the habituation stage, the second is the development stage, the third is the learning stage. The supporting and inhibiting factors for the school literacy movement at SMP HATI Bilingual Boarding School are internal factors. In implementing the school literacy movement in shaping the character of a fond of reading at SMP HATI Bilingual Boarding School Probolinggo Regency. This researcher aims to find 1) To find out the implementation of the school literacy movement SMP HATI Bilingual Boarding School Probolinggo Regency 2) To find out what are the supporting and inhibiting factors for school literacy movement activities at SMP HATI Bilingual Boarding School Probolinggo Regency.